Functional ultrastructure of the midgut of the fire ant Solenopsis saevissima Forel 1904 (Formicidae : Myrmicinae) - Arab, A.; Caetano, F. H. (Faculty Press, 2001)
Solenopsis saevissima has a midgut composed of columnar, regenerative, and goblet cells. The midgut epithelium was covered by a basal lamina. Outside the basal lamina, layers of inner oblique, circular, and outer longitudinal muscles were present. Columnar cells showed a basal plasma membrane containing numerous folds, mitochondria, and the nucleus. Rough endoplasmic reticulum, Golgi bodies, membrane bounded vacuoles, and spherocrystals were found in this region. The apical plasma membrane was constituted by microvilli, which were above a region rich in mitochondria. Regenerative cells were found in groups lying by the basal lamina. Goblet cells were associated with an ion-transporting mechanism between the haemolymph and the midgut epithelium. These cells were lying by the midgut lumen and large microvilli were evident, but the cytoplasmic features were similar to the columnar cells.
Keywords: morphology; columnar cells; Solenopsis saevissima; spherocrystals; active transport